ADIZ (AIR DEFENCE IDENTIFICATION ZONE) DAN GEOPOLITIK RUANG UDARA INDONESIA - Iqbal, Syarif; Mirza, Fajar (Mandala: Jurnal Ilmu Hubungan Internasional, 2024)
This research discusses Indonesia's geopolitical interests in implementing the ADIZ (Air Defense Indentification Zone). ADIZ is an airspace for defense zone recognized by countries and binding as customary international law. This research is qualitative research with secondary data sources in the form of scientific studies, archives, and previous research. Using neorealism theory, the results of the study show that Indonesia's geopolitical interest in the implementation of ADIZ is to ensure Indonesia's security in the midst of anarchic world conditions that result in several potential external threats. The first potential threat is the existence of China's military and economic activities in the South China Sea which affect the surrounding regional countries, especially Southeast Asian countries. Second, China's rise triggered a growing competition between the two major powers, the United States and China, to contain China's power.